The six sigma peterformance handbook - Gupta, Praveen (McGraw-Hill, 2005)
Profits in tough times require prioritization and focus. If properly managed, Six Sigma methods can deliver dramatic improvement by increasing manufacturing and process efficiencies. But nearly 60% of all corporate Six Sigma initiatives fail to yield the desired results -- often companies do not take time to understand what the data in telling them, which is why many Six Sigma projects fail. Written with managers, not statisticians in mind, this reference shows readers how to statistically evaluate a Six Sigma program, identify problems, and make tailor-made adjustments to get the desired results and revitalize a program.